Association Between Chemotherapy and Survival in T1 Colon Cancer With Lymph Node Metastasis: A Propensity-Score Matched Analysis - Yan, Wangxin; Zhou, Huizhen; Shi, Si; Lin, Jixu; Lin, Qiangkang (Frontiers in Oncology, 2021)
This study aimed to comprehensively examine the efficacy of chemotherapy in T1 colon cancer patients with lymph node metastasis. Methods The differences in categorical variables in colon cancer patients according to lymph node status were evaluated by Pearson’s chi-square test. The Kaplan-Meier method was used to assess Cancer-specific survival (CSS) and overall survival (OS) with the log-rank test. Cox proportional hazards models were built, multivariate Cox regression analyses were performed with the hazard ratio (HR) and 95% confidence interval (CI) to identify the potential independent prognostic factors. Propensity score matching was also undertaken to adjust for treatment bias due to measured confounders. Results Younger age (52.2% VS. 43.0% for ≤ 65 years old, p < 0.001), female gender (50.3% VS. 46.8% for female, p < 0.001), more lymph nodes harvested (68.1% VS. 46.6% for ≥12 lymph nodes harvested, p < 0.001), Black race (13.6% VS. 12.0% for the Black race, p < 0.001), and higher tumor grade (14.2% VS. 5.6% for grade III/IV, p < 0.001) were more prone to be diagnosed with lymph node involvement. The receipt of adjuvant chemotherapy following radical surgery significantly reduced the risk of colon cancer-specific mortality by 33.9% after propensity-score matching (HR = 0.661, 95%CI = 0.476-0.917, p = 0.013). Conclusions Younger age, female gender, more lymph nodes harvested, Black race, and higher tumor grade were more prone to be diagnosed with lymph node involvement. The receipt of adjuvant chemotherapy following radical surgery also significantly decreased the risk of colon cancer-specific mortality by 33.9% in T1 colon cancer with lymph node involvement.